2018
DOI: 10.3892/ijo.2018.4567
|View full text |Cite
|
Sign up to set email alerts
|

Cytocidal effects of arenobufagin and hellebrigenin, two active bufadienolide compounds, against human glioblastoma cell line U-87

Abstract: Glioblastoma is the most common and lethal intracranial tumor type, characterized by high angiogenic and infiltrative capacities. To provide a novel insight into therapeutic strategies against glioblastoma, the cytotoxicity of arenobufagin and hellebrigenin was investigated in the human glioblastoma cell line, U-87. Similar dose-dependent cytotoxicity was observed in the cells, whereas no detectable toxicity was confirmed in mouse primary astrocytes. Treatment with each drug downregulated the expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 54 publications
7
41
1
Order By: Relevance
“…Bufadienolides are the major effective constituents of cinobufacini (also known as Huachansu), a well-known Chinese medicine that comes from the dried skin of Bufo bufo gargarizans Cantor, and cinobufacini has been employed to treat patients with different types of cancers such as hepatoma, gallbladder carcinoma, and lung cancer ( 15 – 17 ). We previously clarified that active bufadienolide compounds such as gamabufotalin and arenobufagin showed selective cytocidal effects against intractable cancer cells such as glioblastoma, but minimal effects on human normal peripheral blood mononuclear cells (PBMCs) ( 18 ) and mouse primary astrocytes ( 19 ). Notably, nearly non-toxic gamabufotalin concentrations on PBMCs effectively reduced the percentages of T-regulatory cells (Treg) cells ( 18 ), which has been characterized to play a critical role in limiting antitumor immune response and promoting immunological ignorance in cancer ( 20 – 22 ), suggesting the capability of gamabufotalin to enhance antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bufadienolides are the major effective constituents of cinobufacini (also known as Huachansu), a well-known Chinese medicine that comes from the dried skin of Bufo bufo gargarizans Cantor, and cinobufacini has been employed to treat patients with different types of cancers such as hepatoma, gallbladder carcinoma, and lung cancer ( 15 – 17 ). We previously clarified that active bufadienolide compounds such as gamabufotalin and arenobufagin showed selective cytocidal effects against intractable cancer cells such as glioblastoma, but minimal effects on human normal peripheral blood mononuclear cells (PBMCs) ( 18 ) and mouse primary astrocytes ( 19 ). Notably, nearly non-toxic gamabufotalin concentrations on PBMCs effectively reduced the percentages of T-regulatory cells (Treg) cells ( 18 ), which has been characterized to play a critical role in limiting antitumor immune response and promoting immunological ignorance in cancer ( 20 – 22 ), suggesting the capability of gamabufotalin to enhance antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cell cycle arrest, necrotic and autophagic cell death contribute to cytocidal effect of chemotherapeutic agents ( 19 , 25 – 27 ). Cell cycle is coordinately and tightly regulated by the cyclin-dependent kinases (CDKs) and their associated regulatory cyclins (CDK/Cyclin complexes) ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also studied arenobufagin and hellebrigenin on human glioblastoma cell line U-87 (Han et al. 2018 ). Dose-dependent cytotoxicity was observed in these cells at the compounds concentration of about 20 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, a lot of studies have demonstrated its broadspectrum antitumor activities in cancers such as breast cancer, pancreatic carcinoma, and liver cancer [12][13][14]. We previously found that ARE can induce liver cancer cell apoptosis and autophagy through PI3K/Akt/mTOR signal routing [14]; induce cell cycle arrest and apoptosis in human cervical cancer HeLa cells [15]; have anticancer effect on human esophageal squamous cell carcinoma (its mechanism of exerting anticancer efficacy may be activation of cysteinecontaining aspartate proteolytic enzyme (caspase) by endogenous and exogenous pathways); promote apoptosis of esophageal cancer cells by enhancing caspase phosphorylation and activating p53 signaling [16]; promote apoptosis of human glioblastoma U-87 cells by inhibiting p38MAPK signaling pathway [17]; and inhibit epithelial-mesenchymal conversion by going down the β-catenin pathway, consequently repressing motility and invasiveness of prostate cancer PC3 cells [18]. Nevertheless, the role and mechanisms of ARE on NSCLC remain unclear.…”
Section: Introductionmentioning
confidence: 99%